The Plasma Focus Scaled for Neutrons, Soft X-Rays, Fast Ion Beams, and Fast Plasma Streams - Saw, S. H.; Lee, S. (Kathmandu University Journal of Science, Engineering and Technology, 2014)
Being an intense source of neutrons, soft x-rays, ion beams and fast plasma streams, the plasma focus promises applications such as fusion energy, advanced microlithography, materials synthesizing and testing, radiation diagnostics, medical isotopes and imaging. This paper reviews the scaling laws of neutrons, soft x-rays, ion beams and fast plasma streams derived from extensive numerical experiments conducted over the past 7 years.